The application of the germination index in the assessment of the phytotoxicity of bottom sediments from the Rybnik Reservoir - Szara, Magdalena; Baran, Agnieszka; Tarnawski, Marek; Koniarz, Tomasz (Geology, Geophysics and Environment, 2018)
The aims of the study were to assess the phytoxicity of bottom sediments collected from the Rybnik Reservoir. The water reservoir in Rybnik is located in the Silesian Voivodeship. The reservoir constitutes a part of the technological chain of Elektrownia Rybnik S.A. as a direct receiver of industrial and rainwater sewage, sewage from a water treatment plant, blowdowns from cooling towers, and as an essential source of cooling water. Sediment samples were collected with an Eckman sampler from 33 locations. The toxicity of bottom sediments was determined using the Phytotoxkit direct contact test, carried out for 3 plants: Sorghum saccharatum, Sinapis alba and Lepidium sativum. On the basis of the data received, the germination index (GI) was calculated. We found the mean value of the germination index indicated the dominance of the inhibitory effect of bottom sediments on plant growth. Sorghum saccharatum was the most sensitive to pollutants in sediments, while Lepidium sativum was the least sensitive. The Phytotoxkit is a good tool for assessing the toxicity of bottom sediments.